Adaptation and validation of the European Cyberbullying Intervention Project Questionnaire scale in a sample of Portuguese adolescents - Monteiro, Ana Paula; Fonseca, Daniela; Correia, Elisete (Revista Electrónica Educare, 2025)
Introduction. Cyberbullying has negative consequences for those involved and for the school environment, and it is important to have instruments that help detect and understand this phenomenon. Objective. This research aimed to translate and adapt, for the Portuguese population, the European Cyberbullying Intervention Project Questionnaire (ECIPQ), studying its psychometric properties. Methodology. Quantitative and cross-sectional study in which 440 secondary school students from schools in the north and center of Portugal participated. Result. The confirmatory factor analysis revealed good adjustment indexes allowing to confirm the factorial model of the original instrument consisting of two factors correlated with each other, namely cybervictimization and cyberaggression.  The factors showed good internal consistency. Conclusion. The Portuguese version of the ECIPQ presents good psychometric characteristics, which legitimize its use in research and psychopedagogical intervention.